Maternal Transmission of Human Immunodeficiency Virus to Infants in A Tertiary Care Hospital in Pakistan - Tarar, Shahida Husain; Afzal, Muhammad; Shah, Syed Muhammad Ali; Butt, Zamir; Shah, Saleem Raza; Hassan, Mansoor (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To determine frequency of transmission of HIV from mother to child at Aziz Bhatti Shaheed Teaching Hospital Gujrat. Methodology: Cross-sectional study conducted at Aziz Bhatti Shaheed Teaching Hospital Gujrat in Department of Gynecology and Obstetric Unit II from January 2012 to March 2019 using non-probability consecutive sampling. Patients who tested positive for HIV and reached full term were included. Mothers were started ART at time of diagnosis. Infant prophylaxis was done according to WHO guidelines. Counseling regarding breastfeeding was done. HIV status of infants was noted at 12 weeks after birth. A total of 51 patients were included. SPSS 20.0 was used for data analysis. Results: Fifty-one patients included having mean age 29.45+3.15 years. All patients were diagnosed during pregnancy. ART was initiated in 17(33.3%) in first trimester, 10(19.6%) in second trimester, 20(39.2%) in third trimester and in 4(7.8%) post-partum. At 6 weeks follow up of mothers, 46(90.2%) were stable, 3(5.9%) lost to follow up and 2(3.9%) mothers died post-partum at home. At 12 weeks follow up of infants 39(76.5%) tested negative for HIV, 2(3.9%) were tested positive, 7(13.7%) lost to follow up and 3(5.9%) infants died during this period. In alive and tested infants 2 out of 41 were tested positive, making HIV transmission to children from mothers to be 4.9%. Conclusion: HIV transmission to children form mothers is high in our population and there is need for active screening of all pregnant mothers. Key Words: Mother to Child HIV Transmission, HIV, HIV in Infants, Pregnancy, AIDS